Evaluasi Pelaksanaan Senam sebagai Upaya Preventif terhadap Penyakit Arthritis di Desa Kalukubodo - A. Muflihah Darwis; Dian Saputra Marzuki; Violenialola Fernandes Tangdiesak; Ardaridhayana Ardaridhayana; Diva Fadliah Kusumawardani (Gapenas Publisher, 2022)
One of the efforts to prevent arthritis is to do regular and light exercise to maintain joint flexibility. Regularly doing exercise can reduce joint pain and swelling, relieve stiffness and prevent joint damage. Performing rheumatic exercises is expected to improve the quality of life of the elderly so that the elderly can carry out their daily activities comfortably. The target of the joint gymnastics activity is the people of Kalukbodo Village by using the joint gymnastics mentoring method and interviews. The activity was carried out at the Kalukubodo Village Office on July 1, 2022. The results of the evaluation showed that the residents of Kalukubodo Village still carried out arthritis exercises regularly every week